ANALISIS KELENGKAPAN PENGISIAN INSTRUMEN TENTANG SURVEI PASIEN DALAM UPAYA PENINGKATAN MUTU LAYANAN RAWAT INAP DI RUMAH SAKIT X BEKASI TAHUN 2017 - Maggie Juntiven Manik (Universitas Respati Indonesia, 2019)
Customer satisfaction is the main indicator of the standard of a health facility and is a measure of service quality. Completion of satisfaction survey instruments for the food variables was only 64% who rated it. The purpose of the study is to obtain information and to analyze the incomplete filling of inpatient satisfaction survey in X hospital in Bekasi in giving feedback to the hospital. The informants in the study were 2 people Management, 10 inpatients, 21 nurses inpatients installation. The results of this study provide an illustration that the satisfaction survey instrument didn’t correctly filled and completely filled because the method used is not implemented according to the policy that has been settled. The conclusion of this research is the survey instrument is only 64.35% filled correctly because the instrument is too many so the patients feel like don’t get the explanation or education about the survey instrument. This research suggest that the survey instrument can be revised and made more effective and efficient, being an indicator of service quality, and the explanation of the survey instrument get inside the integrated education communication form.Keywords : Quality of Service, Inpatient, Survey Instruments